Lead evaluation in children's lipsticks through atomic absorption spectrometry - Silvia Cristina Fagundes; Luciana Grazziotin Rossato-Grando; Camila Favretto Souza; Oberdan Fiorentin; Clovia Marozin Mistura; Charise Dallazen Bertol (Drug Analytical Research, 2021)
Lead is a metal with recognized toxicity and it is known that it may be a contaminant in lipsticks. In Brazil, the Health Regulatory Agency (ANVISA) determines that the maximum limit allowed for the presence of lead in lipsticks is 20 ppm. Children are more vulnerable to lead toxicity. The objective of this study was to evaluate the presence of lead in infant lipsticks. Nineteen samples from four different brands sold in Brazil were evaluated. After sample extraction, analyses were performed by graphite furnace atomic absorption spectrometry. Lead was not detected in any of the tested lipsticks. Considering the presence of lead in adult makeup, the present study reinforces the need to use products intended for children considering kids are more vulnerable to lead toxic effects.